Sharia Business Ethics in Capital Market Investment on the Indonesian Stock Exchange Study of the Application of Sharia Principles Bei - Muawari, Lalu Jedi; Ningtias, Karmelia Sasmita; Adinda, Prameswari Cuzenti; Sudianti, Riska; Irsyad, Ziqrurrahman; Nuraini, Nuraini (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Sharia-based investment in the Indonesian capital market has experienced rapid development along with increasing public awareness of the importance of sharia principles in economic activities. This study aims to examine the application of sharia business ethics in investment on the Indonesia Stock Exchange (IDX), especially in stocks listed on the Jakarta Islamic Index (JII) and the Indonesian Sharia Stock Index (ISSI). Using a literature study method, this study explores the application of sharia principles such as fairness, transparency, and the prohibition of usury in capital market investment. The results of the study indicate that the application of sharia business ethics not only strengthens investor confidence but also increases the growth of sharia financial instruments in Indonesia. However, several challenges such as the lack of sharia financial literacy and regulatory barriers still require more attention. This study is expected to contribute to developing a fairer and more inclusive sharia capital market.